Mathematical modelling of the process of the lye treatment of table green olives - M. B. Maldonado; C. A. Zuritz (Grasas y Aceites, 2003)
A diffusion model for a composite-wall, hollow semi-infinite cylinder, consisting of a thin skin and a thicker flesh, with constant flesh and skin effective diffusion coefficients, DL and DS, respectively, was successfully adjusted to the experimental data obtained during the debittering of green olives variety Arauco or Criolla at 15 ºC, 20 ºC and 25ºC and lye concentrations of 1.50 %, 2.25 % and 3.00 % of NaOH. The DL values ranged between 7.18x10-11 and 1.18x10-09 m2/s, and increased with increasing temperature and lye concentration. The DS values were almost two order of magnitude less than the DL values, and also increased with increasing lye concentration and temperature. They ranged between 4.30x10-12 y 9.32 x10-12 m2/s. Activation energies of diffusion of sodium were respectively for the pulp, 85.48, 77.03 and 71.90 kJ/mol, and 30.24; 29.38 and 22.88 kJ/mol for the skin, for lye concentrations of 1.50 %, 2.25 % and 3.00 %.